An Improved and Simplified Propagation System for Pollen-Free Sugi (Cryptomeria japonica) via Somatic Embryogenesis - Maruyama, Tsuyoshi E.; Tsuruta, Momi; Ueno, Saneyoshi; Kawakami, Kiyohisa; Bamba, Yukiko; Moriguchi, Yoshinari (Frontiers in Plant Science, 2022)
Sugi (Japanese cedar, Cryptomeria japonica) is the most important forestry tree species in Japan, covering 44% of the total artificial forest area. Large amounts of pollen released from these forests each spring cause allergic reactions in approximately 40% of the population, which are a serious social and public health problem in Japan. As a countermeasure, there is an urgent need to reforest using male-sterile plants (MSPs; pollen-free plants); however, the production of MSPs via conventional methods is inefficient, time consuming, and requires considerable resources in terms of labor and space. In the present paper, we described an improved and simplified methodology for the efficient propagation of pollen-free Japanese cedar, combining the use of genetic markers (marker-assisted selection or marker-aided selection) for the early selection of male-sterile genotypes and the use of somatic embryogenesis for the clonal mass propagation of seedlings. We describe all the stages involved in the production process of somatic seedlings. Our results demonstrated that this methodology easily and efficiently produces MSPs with a discrimination rate of 100% in a short period of time. Production of 243.6 ± 163.6 cotyledonary embryos per plate, somatic embryo germination and plantlet conversion frequencies of 87.1% ± 11.9% and 84.8% ± 12.6%, respectively, and a 77.6% ± 12.1% survival rate after ex vitro acclimatization were achieved. Moreover, we also describe an easy method for the collection of somatic embryos prior to germination, as well as an efficient and practical method for their storage at 5°C. Finally, a representative schedule for the propagation of pollen-free sugi somatic seedlings is presented as a reference for practical uses. This methodology will definitively help to accelerate the production of C. japonica MSPs across Japan.